LEARNING ASSISTANCE AS AN EFFORT TO IMPROVE LEARNING ACHIEVEMENT - Nandini Rizkya Putri; Atik Dwi Lestari (Sekolah Tinggi Agama Islam Syubbanul Wathon Magelang, 2022)
Al-Qur'an Education Park is a public facility used as a multipurpose building located in Babadan 2 Hamlet, Patent Village, Dukun District. The service activity aims to provide learning assistance for elementary school students in Babadan 2 village to increase the spirit of learning. The small group discussion method can help increase students' enthusiasm for learning. The approach method is the Asset Based Community Development (ABCD) method which focuses on asset development. Achievements in mentoring elementary school students in Babadan 2 hamlet, Patent Village, include: applying discussion learning methods, orientation to students, and assistance in overcoming learning difficulties by forming study groups.